Pengaruh Live Streaming Tiktok Sajodo Snack terhadap Keputusan Pembelian: Survei pada Followers Akun Tiktok @Sajodosnack - Ayu Putri Mungkasih; Jamiati KN (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
The number of micro, small, and medium-sized businesses (MSMEs) active on social media is on the increase. Because of this, many Indonesian MSMEs advertise their wares on social media. The snack food MSME industry is one that is seeing expansion. In recent times, TikTok has gained popularity as a promotional medium that offers cost-effective information delivery. The impact of TikTok on live streaming engagement, which mixes entertainment aspects with commercial messaging, has been the subject of several studies in the marketing literature. The purpose of this research is to find out how much of an effect the TikTok Live streaming account @sajodosnack has on people's inclination to buy. This research used a quantitative technique based on a survey method. The theory utilized includes Live streaming with the dimensions of Perceived Product Quality, Real-Time Interaction, and Host Credibility, and Purchasing Decisions with the dimensions of Problem Recognition, Information Search, Alternative Evaluation, Purchase Decision, and Post-Purchase Behavior. Using a random sample approach, 105 respondents who were fans of the TikTok account @sajodosnack were given questionnaires to fill out in order to gather data. According to the findings, those who participated in the study agreed with the claims made about the TikTok live streaming variable (X). On top of that, all statements pertaining to the purchase choice variable (Y) in the survey were met with favorable responses from respondents. The impact of TikTok live streaming on purchase choices for Sajodo Snack is strongly correlated (r=0.710); live streaming accounts for 50.3% of the total, while other variables account for the remaining 49.7%.